Free Cash Flow and Investment Efficiency of Listed Manufacturing Companies in Nigeria - Kantudu, Aliyu Sulaiman; Umar, Abubakar Sadiq (SEISENSE Journal of Management, 2021)
Purpose- This study aims to determine the relationship between free cash flow and investment efficiency of quoted manufacturing companies in Nigeria. Design- An accounting-based model developed by Richardson (2006) was employed to measure investment efficiency and free cash flow. The population of the study consist of all the listed manufacturing companies in Nigeria. Similarly, the purposive sampling technique was employed to arrive at forty-eight companies for 2008-2018. Findings- The results of the study confirm the agency theory of free cash flow. Hence, it established that there is a positive and robust relationship between free cash flow and overinvestment. Practical Implications- the findings of this study has practical implications to various group of users of financial information such as investors, policymakers and other stakeholders in the listed manufacturing sector in Nigeria. The study recommends that policymakers reduce the cost of debt, and likewise, managers should emphasize the facilitation of equity capital. Originality- To the best of the researcher's knowledge, this is the first study to examine the relationship between free cash flow and investment efficiency in Nigeria.